2014
DOI: 10.1007/s13197-014-1382-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different packaging films on shelf life and quality of peach under super and ordinary market conditions

Abstract: Peach (Prunus persica L. Batsch) fruits of cultivar 'Shan-i-Punjab' were harvested at colour break stage and packed in paper moulded trays followed by wrapping with different packaging films viz. cryovac heat shrinkable RD-106, cling and low density polyethylene (LDPE) film. After packaging, the fruits were stored under two different conditions i.e. super-market conditions (18-20°C; 90-95 % RH) and ordinary market conditions (28-30°C; 60-65 % RH). The fruits were evaluated for various quality attributes period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
5
22
0
Order By: Relevance
“…help in multiplication of micro flora. The increase in decay loss during prolonged storage is in agreement with the earlier findings of Nath et al, (2012) and Kaur et al, (2013) in pear and Mahajan et al, (2015) in peach.…”
Section: Decay Losssupporting
confidence: 92%
“…help in multiplication of micro flora. The increase in decay loss during prolonged storage is in agreement with the earlier findings of Nath et al, (2012) and Kaur et al, (2013) in pear and Mahajan et al, (2015) in peach.…”
Section: Decay Losssupporting
confidence: 92%
“…In our study 'Hisar Safeda' Guava was susceptible to transpiration and indicated PLW of 26 %, yet the effect of individual polythene wrapping was impressive, with a final weight loss of just 3-3.5 % and enhanced the storability of guava. Mahajan et al (2013) detected least PLW (3.5 %) in shrink packed pear fruits as compared to unpacked control fruits (6.20 %). Maximum moisture retention (87.4 %) reported in plastic bag wrapped guava stored at 16°C in shrink wrapped Royal-delicious apples and in Nagpur Mandarin (Miano and Jokhio 2010;Wijewardane and Guleria 2009) may be due to retardation in respiration, evapo-transpiration and metabolic processes.…”
Section: Discussionmentioning
confidence: 89%
“…Besides controlling moisture loss individual shrink wrapping have other beneficial effects like maintenance of firmness, reduction in deformation, alleviation of chilling injury, reduction of decay from secondary infection, delay in colour development and senescence. Shrink film maintained superior quality of pear fruits by significant reductions in weight loss, total soluble solids, desired firmness and extended storage life up to 3 weeks in contrast to LDPE and HDPE films (Mahajan et al 2013). Packaging of apples with CFB boxes, polyethylene liners and shrink wrapped tray in storage conditions (2±1°C, 85-90 % RH) have desired effect on physico-chemical characteristics and retained better storage life (Wijewardane and Guleria 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Various encapsulation methods are available, including 1) physical methods such as spray drying, fluid bed coating, extrusion spheronization, centrifugal extrusion, and processes using the supercritical fluids; 2) physicochemical methods using spray cooling, hot melt coating, ionic gelation, solvent evaporation extraction, and simple or complex coacervation; and 3) chemical methods through interfacial polycondensation, polymerization, and interfacial crosslinking (Munin & Edwards-Lévy, 2011;Shanthi, Gupta, & Mahato, 2010). Amongst, the method of ionic gelation has attracted great interest due to easy to handle, highly compatible, non-toxic, organic solvent free, convenient and controllable (Abdel-Hafez, Hathout, & Sammour, 2014;Mahajan, Dhillon, Kumar, & Singh, 2014;Yoksan, Jirawutthiwongchai, & Arpo, 2010). In the ionic gelation, polysaccharides undergo ionic gelation and precipitate to form spherical microcapsules due to the complexation between oppositely charged species (Racoviţă, Vasiliu, Popa, & Luca, 2009).…”
Section: Introductionmentioning
confidence: 99%